2020
DOI: 10.1111/evj.13297
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative state in equine neonates: Anti‐ and pro‐oxidants

Abstract: Background In newborns, exposure to the extrauterine environment with high oxygen tension and sudden pulmonary adaptation leads to an increase in reactive oxygen species (ROS). ROS have several physiological roles, which are essential for neonatal development, however, when unbalanced, these highly unstable molecules can cause cellular destabilisation, compromising vital processes. Objectives To characterise the oxidative status in healthy equine neonates, evaluating an indicator of lipid peroxidation and both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…This would corroborate the data observed in this study, where we had the highest concentrations of IB at 6, 12, and 24 h of life, and the SOD activity did not vary at these moments. Similar results were found in humans [23] and equine [7] neonates, where no variations were observed in the SOD enzymatic activity, while the indirect bilirubin was elevated.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This would corroborate the data observed in this study, where we had the highest concentrations of IB at 6, 12, and 24 h of life, and the SOD activity did not vary at these moments. Similar results were found in humans [23] and equine [7] neonates, where no variations were observed in the SOD enzymatic activity, while the indirect bilirubin was elevated.…”
Section: Discussionsupporting
confidence: 87%
“…However, at 30 days, there was a significant increase in GPx activity along with a lower concentration of TBARS. Previous studies in horses have demonstrated a significant decrease in TBARS concentrations from 5 min after birth to 72 and 168 h postpartum; this reduction indicates that they showed peripartum peroxidation [7]. In another study, horse neonates showed high levels of TBARS at birth, with a subsequent decrease up to 7 days, and lower GPx activity at birth with an increase at 12 h of life [6].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The oxidative status has also been studied in horses [25][26][27][28][29][30][31][32][33], and there are also a few studies on donkeys [34][35][36]. In horses, studies assessing oxidative status in relation to exercise reported higher concentrations of derived reactive oxygen metabolites (d-ROMs) after sub-maximal exercise on a treadmill, compared to rest [26,27].…”
Section: Introductionmentioning
confidence: 99%